Independent and combined influence of AGTR1 variants and aerobic exercise on oxidative stress in hypertensives - FENTY-STEWART, NICOLA (2009)
Angiotensin II (AngII), via the AngII type 1 receptor (AT(1)R), contributes to oxidative stress. Aerobic exercise training (AEXT) reduces the risk of cardiovascular (CV) disease, presumably by reducing the grade of oxidative stress. We investigated the independent and combined influence of the AGTR1 A1166C and −825 T/A polymorphisms on oxidative stress and plasma AngII responses to AEXT in pre- and stage 1 hypertensives. Urinary 8-iso-PGF(2α) significantly increased with AEXT (p=0.002); however, there were no significant changes in superoxide dismutase activity or AngII levels. There was a significant difference in the change in AngII levels with AEXT between A1166C genotype groups (p=0.04) resulting in a significant interactive effect of the A1166C polymorphism and AEXT on the change in AngII (p<0.05). Only the TT genotype group of the −825 T/A polymorphism had a significant reduction in plasma AngII (p=0.02). Risk allele analysis revealed a significant reduction in plasma AngII (p=0.04) and a significant increase in urinary 8-iso-PGF(2α) (p=0.01) with AEXT in individuals with two risk alleles only. Our findings suggest that variation in the AGTR1 gene is associated with differential changes in plasma AngII but not oxidative stress.